OSHA'S PROPOSED RULE ON INDOOR AIR QUALITY DOCKET NO. H-122 - ADADO,LH; BANZHAF,JF III; BUTLER,WJ; DONLEY,AM; ELY,C JR; GLANTZ,S; GRANSTON,MD; LAUCHNER,WD; MAURER,KR; MICHAELSON,MG; MOTLEY,RL; SHERMAN,SJ; TYSON,PR; VITTONE,JM; WARD,ME; WASSER,NH (Tufts Archival Research Center, 2007)
Marginalia; Series of letters from Philip Morris and opposing council to Judge John Vitone of the U.S. Department of Labor regarding Philip Morris’ accusation of unfairness in the 1994 Indoor Air Quality Hearings. Details OSHA representatives accusation of the cigarette company retreat from the hearing due to fears of answering questions. Includes various deposition transcripts.